2021
DOI: 10.1037/prj0000482
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Veteran X peer-led mental health recovery program: A quasi-experimental study.

Abstract: The inclusion of peer-delivered services in organizations providing behavioral health care has significantly increased in recent years, and substantial resources are being directed toward implementing recovery-oriented mental health services using peer-provided programs. Previous research found that participants in such programs have improved recovery outcomes. While there are demonstrated positive associations between recovery outcomes and peer-provided services, there is limited research on the effectiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Regarding peer workers serving as providers of pre-determined services, 19 of 21 studies focused on the outcomes. These studies typically consisted of high-quality clinical trials or randomized controlled trials (RCTs) comparing peer workers delivering pre-determined services with non-peer workers (Corrigan et al, 2017 ; Crisanti et al, 2019 ; Kidd et al, 2021 ; O’Connell et al, 2018 ; Ranzenhofer et al, 2020 ; Rogers et al, 2016 ; Shaw et al, 2021 ; Simpson et al, 2014 ; Tracy et al, 2011 ) or comparing peer workers as co-facilitators of a pre-determined service with services as usual (Agrawal et al, 2016 ; Cheng & Yen, 2021 ). Some studies also applied qualitative-oriented methods, such as interviews (Beehler et al, 2014 ; Muralidharan et al, 2020 ; Wusinich et al, 2020 ) and a case study (Harris et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding peer workers serving as providers of pre-determined services, 19 of 21 studies focused on the outcomes. These studies typically consisted of high-quality clinical trials or randomized controlled trials (RCTs) comparing peer workers delivering pre-determined services with non-peer workers (Corrigan et al, 2017 ; Crisanti et al, 2019 ; Kidd et al, 2021 ; O’Connell et al, 2018 ; Ranzenhofer et al, 2020 ; Rogers et al, 2016 ; Shaw et al, 2021 ; Simpson et al, 2014 ; Tracy et al, 2011 ) or comparing peer workers as co-facilitators of a pre-determined service with services as usual (Agrawal et al, 2016 ; Cheng & Yen, 2021 ). Some studies also applied qualitative-oriented methods, such as interviews (Beehler et al, 2014 ; Muralidharan et al, 2020 ; Wusinich et al, 2020 ) and a case study (Harris et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…While these clinical trials and RCT studies have been criticized for their lack of attention to core peer work principles when measuring outcomes (King & Simmons, 2018 ), some of them explicitly reported that the pre-defined activities reflected a peer support perspective (Johnson et al, 2021 ; McCarthy et al, 2019 ; Shaw et al, 2021 ; Simpson et al, 2014 ; Thomas & Salzer, 2018 ; Wusinisch et al, 2020 ). Some also included measurements of fidelity to peer support principles before conducting RCTs (Green et al, 2013 ; Kidd et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as one interviewee stated peer interactions should not act to prevent or delay interaction with the community, rather it should act to enable the journey. There is a growing body of research regarding peer led service provision in both the veteran and civilian population (Cheney et al, 2016 ; Shaw et al, 2021 ; Anderson et al, 2022 ; Gettings et al, 2022 ). Although such peer interventions hold great value there is a lack of research into their effectiveness (Ahern et al, 2015 ; Derefinko et al, 2018 ).…”
Section: Discussion and Implications For Clinical Settingsmentioning
confidence: 99%